Evaluasi Hasil Digitalisasi Tugas Akhir Mahasiswa di UPT Perpustakaan Universitas Andalas - Inggi Eka Mei Putri; Desriyeni Desriyeni; Marlini Marlini (Universitas Sebelas Maret Library, 2025)
This study aims to evaluate the practice of digitizing undergraduate theses at the Library of Andalas University as part of the institutional repository development strategy. The research employed a descriptive qualitative approach with data collected through observation, interviews with three librarians and two students, as well as direct involvement of the researcher in the digitization workflow. The findings reveal that the digitization process has been systematically implemented through several stages, including collection identification, document scanning, file editing, metadata preparation, and uploading to the institutional repository scholar.unand.ac.id. The primary objectives of digitization include addressing the limitations of physical storage space, mitigating structural risks caused by geographical conditions, and expanding access to students’ scholarly works. Nevertheless, several challenges persist, such as the absence of formal university-level policies, outdated equipment, technical difficulties in handling large file sizes, and limited staff training. From the user perspective, difficulties were found in slow self-upload processes, unreadable files, and suboptimal search accuracy. Based on these findings, this study emphasizes that evaluating digitization practices not only provides an overview of achievements and obstacles but also generates strategic recommendations for further development. These recommendations include integrating digitization into official university policies, upgrading technological infrastructure, and enhancing staff capacity to ensure that the institutional repository can function optimally as a sustainable medium for preservation and scholarly dissemination.